A report on practice in industry training in fish culture - Garcia, Danilo B. (Miagao, Iloilo College of Fisheries, University of the Philippines, 1978)
Fishing is as old as history of man. In the Genesis God declared that man should have dominion ever the fish of the sea, the fowl of the air, and every living thing that moves upon the earth. And as man found himself standing between and made of his first occupation. Since then, and up to the present time, fishing has been a means of man's livelihood. In all times, in peace and in war, in prosperity and in poverty, man finds fishing feasible. The Philippines is gifted with very long and irregular shorelines forming numerous coves, bays, and gulfs, a number of wide lakes, rivers and streams and other man made fish farming areas, such as ponds and fish pens. The milkfish or "bangus" which is scientifically known as chanos-chanos (forskal) is a unique fish which has a great impact on the economy of the Philippines, wherein about 300 million pesos are invested in its fishery. Chanos chanos is found in the red sea, east coast of Africa, all over the Indian and Pacific Oceans to Hawaii and even to the coast of Mexico. The Philippines appears to be at the center of the range where more fry is taken elsewhere. Thus, the author of this report emphasizes the technical know-how on the handling of "bangus" fry and fingerlings and how to raise and rear them in fishponds and fish pens. This report was made after a training period of 4 months at Mr. Mario Siochi's fishponds and fishpen.
The report on practice in industry training submitted to the University of the Philippines College of Fisheries in partial fulfillment of the requirements for graduation in fish culture course.
Keywords: Fish-culture.